A non-invasive approach to assess texture changes in sous-vide cooked Atlantic mackerel during chilled storage by fluorescence imaging. (October 2018) - Cropotova, Janna; Mozuraityte, Revilija; Standal, Inger Beate; Rustad, Turid
Abstract: The aim of this study was to investigate the potential of fluorescence microscopy coupled with chemical, physical and data analysis methods for reliable and non-invasive detection of changes in texture parameters of sous-vide cooked Atlantic mackerel during chilled storage. Fluorescence micrographs of cook loss and connective tissue of the fish samples after sous-vide treatment at 60 °C and 75 °C for 10, 15 and 20 min taken in the 1st, 3rd and 7th day of chilled storage were acquired. The obtained images were numerically processed and the resulting data was directly correlated (R = 0.960) with the total collagen content determined by a chemical method. Partial least squares analysis was applied to derive statistically significant regression models revealing the influence of each of sous-vide regime parameters on changes in total collagen content and texture parameters of Atlantic mackerel during chilled storage. Results showed that both collagen integrity and firmness of mackerel flesh were significantly (p < 0.05) affected by the temperature of sous-vide treatment and duration of chilled storage, leading to gradual softening of the fish tissue due to degradation of collagenous tissue. Highlights: Fluorescence intensity directly correlated with collagen content. Hardness of fish flesh decreased during sous-vide experiment. Decrease of hardness was correlated with decrease in collagen content. Decrease in cohesiveness was correlated with decrease in total collagen.